Extended application of test results for fire resistance and/or smoke control for door, shutter and openable window assemblies, including their elements of building hardware. Smoke control for doors, shutters, operable fabric curtains and openable windows Part 20, (1st October 2020) - British Standards Institution,
No abstract available